A Fuzzy-based mobility prediction in the IEEE 802.16e - Al-khateeb, Mohammed K.; Hassan Abdalla Hashim, Aisha (2009)
Intersystem mobility having no awkward transitions or indications of disparity, roaming across wireless access networks is one of the main features of Mobile WiMAX. In this paper, we propose a mobility prediction method based on fuzzy logic control and an algorithm similar to the fuzzy c- mean partitioning to predict the movement patterns and handover times by measuring mobile users’ velocity and monitoring the received signal strength of the serving base stations and target base stations simultaneously. With the help of the prediction, reserving the required amount of resources for the upcoming handover event at the target base station can occur before handover initiation and execution. This would grant mobile users of high priority connections (e.g., UGS basedVoIP connection) accessibility to the target base station with no connection termination at various loading situations. The viability and efficiency of the method is demonstrated through experiments conducted with system parameters and propagation model defined by WiMAX Forum. This is to show that the prediction of the future handover times based on predicted received signal strength trend is accurate to maintain the promised QoS level and to reduce the total handover delays caused by layer-3 handover initiation. This allows Layer-3 handover initiation to occur before Layer-2 initiation.